Peningkatan Kesadaran dan Empati Siswa terhadap Bahaya Bullying Melalui Penyuluhan Interaktif - Hayyin, Fajar; Surani, Dewi; Panudju, Andreas Tri; Supriyadi, Supriyadi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Bullying is an aggressive behavior that can have negative impacts on victims, perpetrators, and bystanders. This community service program aimed to increase students’ awareness of bullying, its various forms, and strategies for prevention and intervention. The activities were conducted at junior high schools using interactive counseling, case studies, group discussions, and role-playing methods. Evaluation was carried out through surveys, pre-tests, and post-tests. The results showed a 43.35% increase in students’ understanding. Approximately 91% of students understood the types of bullying, 89% felt more confident in reporting incidents, and 86% demonstrated a better understanding of the bystander's role. Role-playing activities were particularly effective in fostering empathy and social awareness. It is hoped that, through this program, students will be better equipped to recognize and avoid bullying behavior, and contribute to creating a safer, more inclusive, and bullying-free school environment.